Investigation of Antiplasmodial Effects of Terpenoid Compounds Isolated from Myrrh - Greve, Hippolyt L.; Kaiser, Marcel; Schmidt, Thomas J. (Planta Medica, 2020)
As part of our ongoing search for antiprotozoal natural products from plants, we examined different resins from the Burseraceae family. The dichloromethane extract obtained from myrrh, the oleo-gum-resin of Commiphora species, showed promising in vitro activity against Plasmodium falciparum with an IC50 value of 1 µg/mL. Bioactivity-guided fractionation led to the isolation and characterization of 18 sesquiterpenoids, namely, β-elemene (1), elemyl acetate (2), curzerenone (3), 8-hydroxyisogermafurenolide (4), 2-methoxyisogermafurenolide (5), 8-epi-2-methoxyisogermafurenolide (6), furanodienone (7), 1(10)Z,4Z-furanodien-6-one (8), rel-2R-methyl-5S-acetoxy-4R-furanogermacr-1(10)Z-en-6-one (9), (1(10)E)-2-methoxy-8,12-epoxygermacra-1(10),7,11-trien-6-one (10), 2R-methoxyfuranodiene (11), 2-acetyloxyglechomanolide (12), 8-epi-2-acetyloxyglechomanolide (13), (1R,2R,4S)-1,2-epoxyfuranogermacr-10(15)-en-6-one (14), hydroxylindestrenolide (15), isohydroxylindestrenolide (16), myrrhone (17), and myrrhterpenoid O (18). Moreover, nine (nor-)triterpenoids were isolated: mansumbinol (19), mansumbinol epoxide (20), mansumbinone (21), mansumbin-13(17)-en-3,16-dione (22), 3,4-seco-mansumbinoic acid (23), rel-20S-hydroxy-dammar-24-en-3,16-dione (24), rel-(16S,20S)-dihydroxydammar-24-en-3-one (25), cycloart-24-en-1α,2α,3β-triol (26), and 3β-isovaleroyloxycycloart-24-en-1α,2α-diol (27). All compounds were identified by MS and NMR spectroscopic analyses. To the best of our knowledge, compounds 5, 6, 12, 13, 16, 18, and 20 are reported for the first time. All isolated compounds were tested in vitro for activity against P. falciparum and cytotoxicity. The sesquiterpene 7 and the triterpene 25 were the most active compounds found in this study with IC50 values of 7.4 and 2.8 µM, respectively.
Keywords: Myrrh; Commiphora; Plasmodium falciparum; antiprotozoal activity; Burseraceae; terpenoids